PEMODELAN AUDIT MUTU INTERNAL DIBIDANG PENELITIAN MENGGUNAKAN TEKNIK FORWARD CHINING - Nugroho, Nugroho (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Fulfillment of the SN-DIKTI standards which consist of 24 standards is the obligation of universities to implement them and research is part of the tridarma activities of higher education. Evaluation is the most important part that cannot be left out in the quality assurance cycle. Internal Quality Audit is an evaluation process for standard assurance of the Internal Quality Assurance System (SPMI) as a form of effort made by universities to see whether the SPMI standards set by the university are effective or not. This Internal Quality Audit (AMI) model is focused on the field of research carried out by teaching staff at STIE YA Bangko. This internal quality audit, of course, refers to the SPMI standard in the field of research that has been set by STIE YA Bangko. This model is a web-based expert system using the Forward Chaining technique which can be used by auditors to carry out internal quality audits in the research field. This modeling can work well in conducting consultations.